Marketing Georgia-grown, forage-fed beef - Cigainero, Brian S. (Kansas State University, 2011)
The cattle market has drastically changed over the last half century. Today, ranchers and farmers are faced with various governmental regulations as well as fluctuating grain and fuel prices. While beef may still be a commodity, it can be sold in specialized markets, in markets that have enhanced consumer demand. It is nearly impossible for a producer with a small herd to compete with a larger ranch if they are selling their cattle as a commodity. The primary economic objective of the producer is to generate revenue. Producers must be profitable to remain in business as well as provide a livelihood for their family. Providing a quality product is part of the business model. Choice within a marketplace is beneficial for producers and consumers. That said forage-fed beef will prosper in marketplaces where consumers desire their product more than alternate products. If producers are intent on progressively growing their market share, Georgia-grown, forage-fed beef must be marketed correctly. This includes promoting it on a basis of locally grown, pasture raised, and other attributes consumer’s desire. The results of the marketing survey present data that may be helpful when marketing Georgia-grown, forage-fed beef. The weekly consumption of beef products provided insight into the potential scope of the market. Approximately 39 percent of respondents consumed beef products three or more times per week. Additionally, 43 percent of the respondents were not familiar with forage-fed beef. This is a significant share of the market that is possibly open to a new product like Georgia-grown, forage-fed beef. Similarly, traceability of the product was an important feature that customers preferred. In addition to a larger selection of naturally produced beef products, respondents also indicated they were willing to pay more for the product. Approximately 49 percent of the respondents indicated that they would be willing to pay up to a dollar more per pound for Georgia-grown, forage-fed beef. Another 30 percent of the respondents indicated that they would be willing to pay more than $1 per pound for Georgia-grown, forage-fed beef. The results of the survey appear to offer opportunities for producers of Georgia-grown, forage-fed beef to expand their market share.
Keywords: Forage Fed Beef; Agriculture, General (0473); Economics, Agricultural (0503); Management (0454)